Investigating Teachers Grading Perceptions, Current Grading Habits and Their Views Towards Classroom Assessment Grading Practice - Oluchukwu David Okoli; Festus Ebuka Ifejika (JPP (Jurnal Pendidikan dan Pembelajaran), 2022)
This study empirically investigated teachers' perceptions, current assessment grading practices, and views towards classroom assessment grading practice. The study randomly sampled 204 teachers and utilized three questionnaires for data collection. Cronbach Alpha Coefficient established the reliability of the various questionnaires. Frequency counts and percentages were used to answer the study research questions, while Pearson correlation was employed to test the study hypotheses. The study found that teachers do not positively perceive assessment grading practice, included non-achievement factors when grading students' assessments and used subjective knowledge when grading assessments. However, teachers viewed the assessment grading practice as an essential tool for quantification of students learning. Subsequently, significance difference was found between teachers' experience and teachers' perception towards assessment grading practice and views on the classroom importance of assessment grading practice. Nonetheless, no significant difference was found between teachers experience and teachers' current classroom grading habits.